A Justice Reform In Consumer Protection In Development Of Financial Technology - Danang Dwi Cahyo; Bambang Tri Bawono (Universitas Islam Sultan Agung, 2021)
This research aims to analyze consumer protection in the development of fintech. The approach used is sociological juridical. Based on the research conducted, it was found that the implementation of fintech is often used as a cover for fraud supported by cyber bullying. The factors that affect the implementation of debtor protection when they are unable to pay their debts to financial technology institutions are the overlapping rules, the lack of reach of law enforcement in cases of fraud under the guise of financial technology institutions, and the influence of globalization which has resulted in the growth of financial technology institutions becoming increasingly unstable under control. This results in the implementation of financial technology not being in accordance with good ethical principles in making an agreement.